Call to the hunt: the one-note xylophone of the DRC - Volper, Julien (International Library of African Music, 2013)
With these enthusiastic words J. Maes accepted the news from Rev Fr. Roland about a curious musical instrument found in the Sanga territory: the mbila (Figure 1). The interest shown in this one-note instrument is easily explained, as in 1934 the Tervuren museum only possessed three examples of mbila, without any accompanying information. Maes' request as chief conservator of the ethnographic section was met, and Roland sent four well documented examples of mbila.
Keywords: African Music